2019
DOI: 10.3390/ijms20102486
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Proteomic Responses of Mulberry Trees (Morus alba. L.) to Combined Salt and Drought Stress

Abstract: Intensive investigations have been conducted on the effect of sole drought or salinity stress on the growth of plants. However, there is relatively little knowledge on how plants, particularly woody species, respond to a combination of these two stresses although these stresses can simultaneously occur in the field. In this study, mulberry, an economically important resource for traditional medicine, and the sole food of domesticated silkworms was subjected to a combination of salt and drought stress and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 95 publications
0
27
0
Order By: Relevance
“…Jasmonic acid and terpenoids play roles in resistance against Phytophthora cinnamomic in Zea mays roots [25]. Ethylene plays a positive role in adapting mulberry to cope with the drought and salinity condition [26]. Transcription factors are also an important factor of gene expression change [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jasmonic acid and terpenoids play roles in resistance against Phytophthora cinnamomic in Zea mays roots [25]. Ethylene plays a positive role in adapting mulberry to cope with the drought and salinity condition [26]. Transcription factors are also an important factor of gene expression change [27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in trees displaying symptoms of wood decay, large amounts of lignans were observed [36]. Mulberry trees contain large quantities of flavonoids and other secondary metabolites, such as phenylpropanoids and alkaloids, which have wide roles in defenses against biotic and abiotic stresses [26] and have long been used in Chinese traditional medicine for human disease treatment [37]. A large number of flavonoid metabolites from mulberry fruit have been evaluated both in vitro and in vivo for their antioxidant activity [38], such as morcin N [39], anthocyanins [40], and so on.…”
Section: Discussionmentioning
confidence: 99%
“…α-Galactosidase (AGAL) is a key enzyme involved in the breakdown of RFOs [47], and plays a role in producing osmoprotectants that stabilize the membranes and protect cells against oxidative stress [48]. Moreover, α-glucosidase (AGLU) digests carbohydrates, including starch and stable sugar [46]. Thus, the increase in AGAL and AGLU expression observed in this study might help P. crassifolia to resist the cold stress at the higher elevations.…”
Section: Changes Of Genes Involved In C Assimilation and Metabolism Imentioning
confidence: 66%
“…Thus, the increase in AGAL and AGLU expression observed in this study might help P. crassifolia to resist the cold stress at the higher elevations. However, the expression of GOLS1 (encoding galactinol synthase 1), which is the first committed enzyme in the RFO synthesis pathway [46], decreased with the increasing elevations. These results indicated that the RFO pathway might play a crucial role in the response of P. crassifolia to elevation changes.…”
Section: Changes Of Genes Involved In C Assimilation and Metabolism Imentioning
confidence: 99%
See 1 more Smart Citation